Additions to the avifauna of Ite Wetlands, south coast of Peru - Vizcarra, Jhonson K. (2009)
The present work reports nine new records of birds species for Ite Wetlands. The species were observed between July of 2008 and June of 2009. These records increase the existent list up to 139 birds species and contribute to justify the importance of this ecosystem for the conservation.